Prevalence of Mycobacterium avium subsp. paratuberculosis infection in sheep flocks from three regions of Antioquia, Colombia - Hernández-Agudelo, Miguel; Collado, Bernardita; Tejeda, Carlos; Ramírez-Vásquez, Nicolás F.; Fernández-Silva, Jorge A.; Salgado, Miguel A. (Austral Journal of Veterinary Sciences, 2021)
Paratuberculosis or Johne's disease is a slow-developing infectious disease caused by Mycobacterium avium subsp. paratuberculosis (MAP) affecting mainly domestic ruminants and producing a significant economic threat to livestock production systems. Although reports on paratuberculosis in small ruminants in Colombia are very scarce, the Colombian sheep industry has identified paratuberculosis as one of the causes of its low development. There have been reports of MAP infection in sheep flocks, mainly in the Cundiboyacense Plateau and the Bogotá savannah, but the prevalence of MAP infection in sheep and goat populations in Colombia is yet unknown. Therefore, the present study aimed to accurately estimate the prevalence of MAP infection at flock level in a sheep population of 24 flocks located in three regions of the province of Antioquia, Colombia. ELISA test as well as culture and direct qPCR were used as diagnostic tools. Overall, 456 blood serum samples were analysed and at least one seropositive animal was found in 17 (70% IC: 51.2-0.90) out of the 24 study flocks and, in total, 37 animals showed positive ELISA results (8% IC: 5.5-10.5). Regarding MAP direct detection, 90 faecal pools from the 24 flocks were cultured and subjected to qPCR diagnosis. Both direct qPCR and culture detected 25 (27.7%) and 64 (71.1%) faecal pools as MAP positive, respectively. More specifically, MAP positive pools were detected in 45.8% (IC: 24.3-67.3) and 83.3% (IC: 67.3-99.3) of the flocks by direct qPCR and culture, respectively. MAP infection is widespread in sheep flocks in the study regions and the combination of several diagnostic tests was necessary to achieve a more accurate and precise infection detection of this important pathogen.